Contributions of dsRNases to differential RNAi efficiencies between the injection and oral delivery of dsRNA in Locusta migratoria. Issue 6 (8th January 2019) - Song, Huifang; Fan, Yunhe; Zhang, Jianqin; Cooper, Anastasia MW; Silver, Kristopher; Li, Daqi; Li, Tao; Ma, Enbo; Zhu, Kun Yan; Zhang, Jianzhen
Abstract: BACKGROUND: The efficiency of RNA interference (RNAi) varies considerably among different insect species, and there is growing evidence to suggest that degradation of double‐stranded (dsRNA) prior to uptake is an important factor that limits the efficiency of RNAi in insects. In Locusta migratoria, RNAi is highly efficient when dsRNA is delivered by injection, but not by feeding. However, detailed mechanisms causing such differential RNAi efficiency are still elusive. RESULTS: We identified and characterized the full‐length complementary DNAs (cDNAs) of two new dsRNA nuclease (dsRNase) genes from L. migratoria, which were named LmdsRNase1 and LmdsRNase4 . Transcript analyses revealed that LmdsRNase1 and LmdsRNase4 were highly expressed in hemolymph with relatively lower expression in other tested tissues. Our study using heterologously expressed LmdsRNase1 and LmdsRNase4 fusion proteins showed that LmdsRNase1 can degrade dsRNA rapidly at an optimal pH of 5, whereas LmdsRNase4 had no activity at any of the pH values examined. In comparing the substrate specificity of the four LmdsRNases, we found that only LmdsRNase1 and LmdsRNase2 digested dsRNA; however, our experiments suggested that the physiological pH of hemolymph (7.0) suppresses LmdsRNase1 activity permitting significant dsRNA stability in this tissue. Conversely, the physiological pH of midgut juice (6.8) is ideal for LmdsRNase2 activity, resulting in degradation of dsRNA in midgut. CONCLUSION: The physiological pH of different insect tissues or compartments can significantly alter the stability of dsRNA by influencing LmdsRNase activity in L. migratoria . Thus, new strategies to overcome such obstacles are expected to help implement RNAi‐based technologies for insect pest management. © 2018 Society of Chemical Industry Abstract : In Locusta migratoria, RNA interference (RNAi) efficiencies are high when double‐stranded RNA (dsRNA) is delivered by injection due to the extended persistence of dsRNA in hemolymph, but low when ds RNA is delivered by feeding due to the limited persistence of dsRNA in midgut.